The Effects of Nano Fillers on Space Charge Distribution in Cross-Linked Polyethylene - A. N. Ramani; A. M. Ariffin; Gobinath Vijian; Ahmad Basri Abd Ghani (Institute of Advanced Engineering and Science, 2017)
The performance of polymeric insulation will be distorted by the accumulation of space charge. This will lead to local electric field enhancement within the insulation material that can cause degradation and electrical breakdown. The introduction of nanofillers in the insulation material is expected to reduce the space charge effect. However, there is a need to analyze potential nanofillers to determine the best option. Therefore, the objective of this research work is to examine two types of nanofillers for Cross-Linked Polyethylene (XLPE); Zinc Oxide (ZnO) and Acrylic (PA40). The effects of these nanofillers were measured using the Pulsed-Electro Acoustic (PEA) method. The development of space charge is observed at three different DC voltage levels in room temperature. The results show that hetero charge distribution is dominant in pure XLPE materials. The use of both nanofiller types have significant effect in decreasing the space charge accumulation. With nanofillers, the charge profile changed to homo-charge distribution, suppressing the space charge formation. Comparisonbetween both the nanofillers show that PA40 has better suppression performance than ZnO.